Effects of task and environmental constraints on axial kinematic synergies during the tennis service in expert players - Shafizadeh, M.; Bonner, S.; Barnes, A.; Fraser, J. (European Journal of Sport Science, 2020)
The aims of this study were to examine the effects of task and environmental constraints on axial synergies and to find an association between synergies and arm acceleration as a performance variable. Participants of this study were 10 expert tennis players (age: 34.4 ± 7.46) who voluntarily took part and executed 60 serves under two different conditions: no-opponent and opponent. An inertial motion unit (IMU) capture system was used to calculate the 3D angular joint motions in the neck, back and lumbar segments. The results of the principal component analysis showed that the redundancy in the axial segments is decomposed into 2 main synergies that are responsible for the loading (backward swing) and firing phase (forward swing). The total variance and loading synergy variance were significantly lower in the topspin service than other service types. The emerged firing synergy was strongly associated with the arm acceleration regardless of service type. In conclusion, the effective strategy to utilise the axial motions in the trunk is through creating functional synergies that have a flexible role based on the type of service and conditions. The topspin service showed less coordination variability relative to other types of service and serving in the opponent condition required participants to change the nature of synergy among the axial segments. These findings support the design of practice that emphasises the importance of more realistic contexts with special attention given to the order of different service types.